2023
DOI: 10.1111/sjop.12992
|View full text |Cite
|
Sign up to set email alerts
|

The effect of emotion recognition and mindfulness on depression symptoms: A case–control study

Orkun Aydın,
Selma Tvrtkovic,
Elif Çakıroğlu
et al.

Abstract: Abnormalities in emotion recognition (ER) are frequently reported in depression, with lower recognition accuracy in patients with major depressive disorder (MDD) when compared to healthy individuals. Mindfulness was found to directly impact the severity of depressive symptoms, by recognizing negative cognitions and dysfunctional reactions. The aims of this study were to compare ER and mindfulness levels between MDD patients and healthy controls (HCs), as well as to examine whether ER and mindfulness are relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Nonreactivity was associated with reduced rumination and less negative bias, negatively correlated with anterior insula activation during negative stimuli engagement [27]. Furthermore a casestudy by Aydın et al (2023) with 69 MDD patients and 93 healthy controls suggested that non-reactivity, in contrast to other facets of mindfulness, is stronger corelated with the intensity of depressive symptoms in individuals diagnosed with MDD. Emphasizing this specific facet of mindfulness has the potential to generate improved results in alleviating depressive symptoms [28].…”
Section: Structural and Functional Effects Of Mbis On The Human Brainmentioning
confidence: 93%
See 1 more Smart Citation
“…Nonreactivity was associated with reduced rumination and less negative bias, negatively correlated with anterior insula activation during negative stimuli engagement [27]. Furthermore a casestudy by Aydın et al (2023) with 69 MDD patients and 93 healthy controls suggested that non-reactivity, in contrast to other facets of mindfulness, is stronger corelated with the intensity of depressive symptoms in individuals diagnosed with MDD. Emphasizing this specific facet of mindfulness has the potential to generate improved results in alleviating depressive symptoms [28].…”
Section: Structural and Functional Effects Of Mbis On The Human Brainmentioning
confidence: 93%
“…Furthermore a casestudy by Aydın et al (2023) with 69 MDD patients and 93 healthy controls suggested that non-reactivity, in contrast to other facets of mindfulness, is stronger corelated with the intensity of depressive symptoms in individuals diagnosed with MDD. Emphasizing this specific facet of mindfulness has the potential to generate improved results in alleviating depressive symptoms [28]. Kang et al (2013), in their cross-sectional study, used diffusion tensor imaging and cortical thickness mapping to explore structural changes in gray and white matter associated with meditation.…”
Section: Structural and Functional Effects Of Mbis On The Human Brainmentioning
confidence: 99%